Cuisine Prediction Based On Ingredients Using Algorithm (International Journal of Advanced Research in Science, Management and Technology, 2023)
The cooking and recipe sharing has been a common thing done now a days. The resulting huge collection of recipes and ingredients helps us to understand the basics of cooking as well as food pairing. With the increasing popularity of food based and recipe sharing, there have been several platforms that have come up with cooking suggestion procedures or recipe engines. Even though this recommendation system suggests recipes, it is not able to exploit the correlation of ingredients with their cuisines. In proposed system, we aim to predict the cuisine based on ingredients as input. The user will get predicted cuisine as well as they will get to see the recipe of the dish. The system will make use of machine learning algorithm such as Naïve Bayes.
Keywords: food pairing, correlation of ingredients, cuisines. machine learning, Naïve Bayes